Feeding behavior and productive performance of steers fed pearl millet grain-based diets containing proportions of babassu mesocarp bran - Alencar,Wanderson Martins (2015)
ABSTRACT The objective of this study was to evaluate the feeding behavior and feedlot productive performance of dairy-origin steers fed for 84 days ground pearl millet grain-based diets with 0, 120, 240, 360, and 480 g kg-1 of babassu mesocarp bran (BMB) and a standard diet based on ground corn. Thirty Holstein-Zebu steers with average initial body weight of 371.02±27 kg were used. The experimental design was completely randomized, with five replications. Dry matter intake showed better fit with the quadratic regression equation with the inclusion of BMB, reaching a maximum value in diets with 360 g of this by-product. There was no difference for dry matter intake between pearl millet- and corn-based diets. There was no difference in total digestible nutrients intake between diets. The digestibility coefficient of organic matter decreased linearly with the increase in the dietary level of BMB. The digestibility coefficient of organic matter was not different between corn and millet diets. There was no difference in feeding time between diets. Total requirement of metabolizable energy increased linearly with inclusion of BMB. However, total requirements of metabolizable energy did not differ between the corn- and pearl millet-based diets. Average daily gain decreased linearly with the increase in BMB, with adjustment forced by the sharp decline of this variable in diets with 480 g of BMB. There was no difference in average daily gain between corn- and pearl millet-based diets. The inclusion of levels above 360 g of babassu mesocarp bran in pearl millet-based diets reduces the supply of metabolizable energy and the productive performance of feedlot dairy steers.